The retributive emotions: passions and pains of punishment - Holroyd, Jules (Routledge, 2010)
It is not usually morally permissible to desire the suffering of another person, or to act so as to satisfy this desire; that is, to act with the aim of bringing about suffering. If the retributive emotions, and the retributive responses of which they are a part, morally permitted or even required, we will need to see what is distinctive about them. One line of argument in this paper is for the conclusion that a retributive desire for the suffering of the wrong-doer, and the aim to bring this about, can (contra recent arguments from Hanna 2008) be morally justified. It has been suggested that by reflecting on the role of the retributive emotions in interpersonal relationships, and the alleged legitimacy of the aim for the suffering of the wrong-doer within them, support can be garnered for retributive practices of punishment by the state (Duff 1986 and 2001, Bennett 2002 and 2003). The conclusion of the second line of argument in the paper is that whilst the retributive responses can permissibly aim at suffering, the way in which this is so in interpersonal relationships cannot provide support for retributive state punishment.